Quality of Life among Post CABG Patients - Ambina K.1 , Shalimol U.S.2 , Anjana A.P.2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Coronary artery bypass grafting (CABG) surgery is one among the most common proceduresperformed in the world, and it is one of the possible treatments for coronary artery disease (CAD). Althoughthe effectiveness of coronary artery bypass grafting (CABG) is being evaluated in terms of mortality,complications or recurrence of symptoms, empirical studies assessing the change in patients quality of life(QOL) after CABG need to be studied as findings keep changing as time progress. A systematic analysisof how well the patient is considering a multiple variable need to be studied which has greater impact inimproving the overall performance of the patients after CABG.Aim: Aim of the study is to assess the quality of life among post coronary artery bypass grafting (CABG)patients.Method: A quantitative approach with a descriptive design using a non-probability convenience samplingtechnique was used to collect data from 101 post CABG patients. The setting used for the study was CVTSOPDs at AIMS, Kochi. A standardized quality of life questionnaire (SF-36) along with a semi-structuredquestionnaire to assess socio-demographic and clinical data.Results: The study result showed that the majority of samples (97%) had good QOL with mean score of69.22. PCS (96%) showed higher value than MCS (68. 3). A significant association found between QOL andsocio-demographic variables like occupation (p=0.018).Conclusion: Overall QOL improved one year after CABG.